2018
DOI: 10.1111/pcmr.12748
|View full text |Cite
|
Sign up to set email alerts
|

Instability of BLOC‐2 and BLOC‐3 in Chinese patients with Hermansky‐Pudlak syndrome

Abstract: Hermansky‐Pudlak syndrome (HPS) is a rare recessive disorder characterized by oculocutaneous albinism (OCA) or ocular albinism (OA), bleeding tendency, and other symptoms due to multiple defects in tissue‐specific lysosome‐related organelles. Ten HPS subtypes have been characterized with mutations in HPS1 to HPS10, which encode the subunits of BLOC‐1, ‐2, ‐3, and AP‐3. Using next‐generation sequencing (NGS), we have screened 100 hypopigmentation genes in OCA or OA patients and identified four HPS‐1, one HPS‐3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Altogether, reduced skin and iris pigmentation, red-eye effect and reduced retinal pigment on fundoscopic examination, and the apparent absence of bleeding tendency are consistent with a mild OCA in pink-eye cats. This phenotype is also consistent with a HPS type 5, as variants in HPS5 in human patients are associated with a spectrum of phenotypes combining OCA or OA with or without visual impairment, bleeding diathesis and colitis (Botero et al, 2018;Michaud et al, 2017;Wei et al, 2019).…”
Section: F I G U R Esupporting
confidence: 74%
“…Altogether, reduced skin and iris pigmentation, red-eye effect and reduced retinal pigment on fundoscopic examination, and the apparent absence of bleeding tendency are consistent with a mild OCA in pink-eye cats. This phenotype is also consistent with a HPS type 5, as variants in HPS5 in human patients are associated with a spectrum of phenotypes combining OCA or OA with or without visual impairment, bleeding diathesis and colitis (Botero et al, 2018;Michaud et al, 2017;Wei et al, 2019).…”
Section: F I G U R Esupporting
confidence: 74%
“…Candidate genes for new HPS subtypes may include genes affected in mouse models of HPS that do not yet have a human counterpart (Table 1) | 569 (Lasseaux et al, 2018). A similar study of 21 Arabian individuals with ocular hypopigmentation identified 10 HPS subjects (Khan et al, 2016), a study of 46 Japanese cases with (OCA-1 and HPS-1 negative) albinism identified nine HPS subjects (Okamura et al, 2019), and a study of Chinese hypopigmentation cases identified 10 HPS subjects (Wei et al, 2019). Similarly, targeted sequencing of a cohort of 159 cases with bleeding, thrombotic, and platelet disorders identified six HPS individuals (Simeoni et al, 2016).…”
Section: Diagnosis Of Hpsmentioning
confidence: 99%
“…Immunoblotting of cultured skin fibroblast or platelet‐rich plasma extracts has also proven helpful to determine or validate the HPS subtype. HPS mouse and human studies have shown that a defect in one HPS protein leads to destabilization of the entire protein complex, that is AP‐3, BLOC‐1, ‐2, ‐3 (Ammann et al, 2016; Dell'Angelica et al, 1999; Huizing et al, 2002; Li et al, 2003; Wei et al, 2019). Therefore, the use of immunoblotting with an antibody against one subunit of the complex (AP‐3 and BLOC‐1,‐2,‐3) allows determination of which complex is defective in unclassified HPS subjects, reducing subsequent sequencing of genes encoding the corresponding subunits (Carmona‐Rivera, Hess et al, 2011; Nazarian et al, 2008; Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Patients recruited in this study were diagnosed with HPS-1 at Beijing Tongren Hospital from 2013 to 2018. Diagnosis of HPS was based on clinical manifestations, absence of platelet dense granules under electron microscopy, loss of platelet HPS1 or HPS4 protein by Western blotting ( 18 ). Mutations of the HPS1 gene confirmed the diagnosis of HPS-1 by next-generation sequencing ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…HPS-1 is the predominant subtype accounting for 47.5% of reported HPS cases in the Chinese population (18). HPS1 and HPS4 proteins are found in the BLOC-3 complex.…”
Section: Introductionmentioning
confidence: 99%